A comparison of the physiological response to simulated altitude exposure and r-HuEpo administration - Ashenden, M. J.; Hahn, A. G.; Martin, D. T.; Logan, P.; Parisotto, R.; Gore, C. J. (Journal of Sports Sciences, 2001)
Concerns have been raised about the morality of using simulated altitude facilities in an attempt to improve athletic performance. One assumption that has been influential in this debate is the belief that altitude houses simply mimic the physiological effects of illegal recombinant human erythropoietin (r-HuEpo) doping. To test the validity of this assumption, the haematological and physiological responses of 23 well-trained athletes exposed to a simulated altitude of 2650-3000 m for 11-23 nights were contrasted with those of healthy volunteers receiving a low dose (150 IU x kg(-1) per week) of r-HuEpo for 25 days. Serial blood samples were analysed for serum erythropoietin and percent reticulocytes; maximal oxygen uptake (VO2max) was assessed before and after r-HuEpo administration or simulated altitude exposure. The group mean increase in serum erythropoietin (422% for r-HuEpo vs 59% for simulated altitude), percent reticulocytes (89% vs 30%) and VO2max (6.6% vs -2.0%) indicated that simulated altitude did not induce the changes obtained with r-HuEpo administration. Based on the disparity of these responses, we conclude that simulated altitude facilities should not be considered unethical based solely on the tenet that they provide an alternative means of obtaining the benefits sought by illegal r-HuEpo doping.